Evaluation of a multinational, multilingual vaccine debate on Twitter. Issue 50 (7th December 2016) - Becker, Benedikt F.H.; Larson, Heidi J.; Bonhoeffer, Jan; van Mulligen, Erik M.; Kors, Jan A.; Sturkenboom, Miriam C.J.M.
Highlights: Twitter messages can indirectly reflect public opinion about vaccine issues or events. Most messages were created by private persons. The debate focuses on local and current events. Abstract: Background: Public confidence in an immunization programme is a pivotal determinant of the programme's success. The mining of social media is increasingly employed to provide insight into the public's sentiment. This research further explores the value of monitoring social media to understand public sentiment about an international vaccination programme. Objective: To gain insight into international public discussion on the paediatric pentavalent vaccine (DTP-HepB-Hib) programme by analysing Twitter messages. Methods: Using a multilingual search, we retrospectively collected all public Twitter messages mentioning the DTP-HepB-Hib vaccine from July 2006 until May 2015. We analysed message characteristics by frequency of referencing other websites, type of websites, and geographic focus of the discussion. In addition, a sample of messages was manually annotated for positive or negative message tone. Results: We retrieved 5771 messages. Only 3.1% of the messages were reactions to other messages, and 86.6% referred to websites, mostly news sites (70.7%), other social media (9.8%), and health-information sites (9.5%). Country mentions were identified in 70.4% of the messages, of which India (35.4%), Indonesia (18.3%), and Vietnam (13.9%) were the most prevalent. In the annotated sample, 63% of the messages showed a positive or neutral sentiment about DTP-HepB-Hib. Peaks in negative and positive messages could be related to country-specific programme events. Conclusions: Public messages about DTP-HepB-Hib were characterized by little interaction between tweeters, and by frequent referencing of websites and other information links. Twitter messages can indirectly reflect the public's opinion about major events in the debates about the DTP-HepB-Hib vaccine.